Penerapan Manajemen Sumber Daya Manusia Dalam Meningkatkan Kompetensi Guru Madrasah Aliyah di Bengkulu - Lilis Merlita; Damas Ahmad Yunus; Rahmuje Emawanalu (Al-Khair Journal: Management Education, 2023)
Abstract: Madrasah human resources still create disparities in teacher competence as a profession, marked by some madrasah aliyah teachers experiencing difficulties in improving their competence and other teachers being able to work professionally according to the teaching profession. The aim of this research is to describe and analyze the application of human resource management in improving the competency of Bengkulu City Aliyah Madrasah teachers. Using descriptive qualitative methods. The sources of information in this research use various sources, both online media data and print media data. Includes scientific books, national and international scientific articles related to the application of human resource management in improving teacher competency. The research results show that; (1) human resource management has been implemented. It can be seen that there has been a planning program for developing teacher competency, organization has been carried out for teachers by giving them main tasks, functions and responsibilities as professional staff, the learning process has been carried out in accordance with the main tasks, functions and responsibilities of each teacher. , and supervision and control of teachers has been carried out; (2) teacher competence has increased in terms of personality, pedagogical, social and professional competence, but is not yet optimal because teachers are rarely given professional education or training; and (3) the application of human resource management can improve teacher competency through teacher academic qualifications, education and training, certification tests, and providing opportunities for learning improvement. Thus it can be concluded that the application of human resource management can increase teacher competence. So it can be suggested, to improve teacher competence, implement human resource management in madrasas.Keywords: Application, Human Resource Management, Teacher Competency, Madrasah Aliyah Abstrak: Sumberdaya manusia madrasah masih menciptakan ketimpangan dalam kompetensi guru, ditandai dengan sebagian guru madrasah aliyah mengalami kesulitan dalam meningkatkan kompetensinya dan sebahagian guru yang lain mampu bekerja secara profesional. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis penerapan manajemen sumberdaya manusia dalam meningkatkan kompetensi guru madrasah Aliyah di Kota Bengkulu. Menggunakan metode kualitatif deskriptif. Sumber informasi dalam penelitian ini, menggunakan berbagai sumber, baik data media online maupun data media cetak. Meliputi buku-buku ilmiah, artikel ilmiah baik nasional maupun internasional yang terkait tentang penerapan manajemen sumberdaya manusia dalam meningkatkan kompetensi guru. Hasil penelitian menunjukkan bahwa; (1) manajemen sumberdaya manusia telah diterapkan terlihat telah ada program perencanaan untuk pengembangan kompetensi guru, telah dilakukan pengorganisasian kepada guru melalui pemberian tugas pokok, fungsi dan tanggungjawabnya sebagai tenaga professional, telah dilaksanakan proses pembelajaran sesuai tugas pokok, fungsi dan tanggungjawab guru masing-masing, dan telah dilakukan pengawasan dan pengendalian terhadap guru; (2) kompetensi guru sudah meningkat dilihat dari kompetensi kepribadian, pedagogic, sosial dan kompetensi professional, namun belum optimal dikarenakan gruru-guru jarang diberi pendidikan profesi atau diklat; dan (3) penerapan manajemen sumberdaya manusia dapat meningkatkan kompetensi guru melalui kualifikasi akademik guru, pendidikan dan pelatihan, uji sertifikasi, dan memberikan kesempatan perbaikan pembelajaran. Dengan demikian dapat disimpulkan bahwa penerapan manajemen sumberdaya manusia dapat meningkatkan kompetensi guru. Sehingga dapat disarankan, untuk meningkatkan kompetensi guru, maka terapkanlah manajemen sumberdaya manusia di madrasah.Kata kunci: Penerapan, Manajemen Sumberdaya Manusia, Kompetensi Guru, Madrasah Aliyah